The Penitentiary Center in the State of Mexico - García Ramírez, Sergio (1969)
This paper begins by describing the situation and problems that afflicted the Mexican prison system during the 1960s. According to the author, the critical state of Mexican prisons led to the establishment of a new system for the treatment of inmates. Thus, a penitentiary system was implemented that focused mainly on the resocialization of the inmate, as well as the promotion of his or her social reintegration. To this end, it sought to reverse the situation by reforming the prison regime, restructuring the penitentiary center, offering medical care, especially psychiatric and psychological care, establishing different work areas, and emphasizing the education of inmates. Furthermore, the benefits not only covered the inmates, but also the prison staff, who had access to the teaching and research institute of the penitentiary center. As the author points out, these modifications were recognized by national and international jurists and criminologists, who considered the Mexican penitentiary center to be one of the most revolutionary.